The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/dev.1007
|View full text |Cite
|
Sign up to set email alerts
|

Visual‐preference and operant measures of infant memory

Abstract: In three experiments with sixty 3- and 6-month-olds, we examined whether operant and visual-preference measures of retention are equivalent. Infants learned to move a mobile by kicking and then received a paired-comparison test with the familiar (training) mobile and a novel one. Kicking above baseline was the direct measure of retention, and longer looking at the novel mobile was the visual-preference or inferred measure. Retention was tested 1 day after training (Experiment 1) or reactivation (Experiment 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
(56 reference statements)
1
10
0
Order By: Relevance
“…In those experiments, infants recognized similarities and differences in details such as the color of elements of the objects when items were encountered in the same experimental session (Needham et al, 2005), but they noticed only general similarities when items were encountered over a 24 hour delay (Dueker et al, 2003). Such findings are consistent with work revealing that infants' visual short-term memory capacity is limited (Ross-Sheehy et al, 2003) and their long-term memories are less detailed (Wilk et al, 2001). We cannot say for certain that the memory system responsible for these effects in short-or long-term memory, but the current manipulation of reducing the amount of time infants are required to remember an item from a few seconds to essentially zero is most compatible with theories of working or short-term memory (see Oakes & Bauer, 2007).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In those experiments, infants recognized similarities and differences in details such as the color of elements of the objects when items were encountered in the same experimental session (Needham et al, 2005), but they noticed only general similarities when items were encountered over a 24 hour delay (Dueker et al, 2003). Such findings are consistent with work revealing that infants' visual short-term memory capacity is limited (Ross-Sheehy et al, 2003) and their long-term memories are less detailed (Wilk et al, 2001). We cannot say for certain that the memory system responsible for these effects in short-or long-term memory, but the current manipulation of reducing the amount of time infants are required to remember an item from a few seconds to essentially zero is most compatible with theories of working or short-term memory (see Oakes & Bauer, 2007).…”
Section: Discussionsupporting
confidence: 77%
“…Detecting similarities and differences between items encountered at different times requires that the memory for one item is compared with a second item currently in view. Because young infants' shorter-term memory abilities are limited (Rose, Feldman, & Jankowski, 2001; Ross-Sheehy, Oakes, & Luck, 2003) and their longer-term memories are less detailed than are the longer-term memories of older infants (Wilk, Klein, & Rovee-Collier, 2001), young infants may not make effective comparisons between a remembered item and another item. Indeed, Needham and her colleagues observed that infants detected different commonalities among items as a function of the amount of time between encounters with those items.…”
mentioning
confidence: 99%
“…It is important to remember, however, that despite the manipulations of spatial and temporal relations in these studies, visual and proprioceptive inputs were nevertheless conjugately related in both experiments. Indeed, there is a great deal of research by Rovee-Collier and her colleagues (e.g., Bhatt, Wilk, Hill, & RoveeCollier, 2004;Hartshorn & Rovee-Collier, 2003;Hildreth, Sweeney, & Rovee-Collier, 2003;Rovee-Collier & Barr, 2001;Rovee-Collier & Gekoski, 1979;Rovee & Rovee, 1969;Wilk, Klein, & Rovee-Collier, 2001, for classic and more recent reviews) suggesting that even very young infants are sensitive to conjugate relations in learning and memory contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is difficult to fully answer this question, the obvious methodological and procedural differences between these two lines of work, such as the use of preferential looking versus an operant conditioning technique, the length of the training phases/trials, differences in the availability of simultaneous visual and proprioceptive information, and so on, clearly plays some role here. And, in fact, Wilk et al (2001) demonstrated that such methodological differences are critical. In a comparison of visual preference and operant-conditioning techniques, infants showed evidence of more sophisticated abilities using operantconditioning methods than they did in a preferential looking paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…"What was the point of encoding and storing information about an event that will not be attended to again until it is forgotten?" At the same time, she questioned the value of novelty detection as a measure of long-term memory, arguing that distraction by novel stimuli tells us nothing about what infants may or may not remember about familiar ones, particularly over the long term (Rovee-Collier, 2001;Rovee-Collier & Hayne, 1987;Wilk et al, 2001). In her view, the VRM paradigm provided a measure of novelty detection, distraction, vigilance, information processing, or short-term memory, which underpinned the concurrent and long-term relation between VRM performance and more standard measures of IQ (e.g., Fagan, 1984;Rose & Feldman, 1995;Rose & Wallace, 1985).…”
Section: In Contrast To the Recognition Memory Exhibited By The 2-andmentioning
confidence: 99%